SMART LOCK SYSTEM USING OTP - Narayana, Dr.V.A; RAJU, K.; RAO, B.VENKATESWER; VARSHITHA, T. LAXMI; SACHIN, B. (The journal of contemporary issues in business and government, 2022)
Humans have invented locks since ancient times, to use them to protect their privacy and personal belongings. They are constantly evolving over the ages for better protection. But the problem is that locking the door these days is not safe and can be easily bypassed. Our doors can be forgotten, and this is a common occurrence for most people. Locks are trying these days to depends on technology by using a code or phone or by card to make our things safer. But there are limits, which are the lack of features to be combined in one place. also, the lack of high-security features. To solve this problem, we need to combine all the modern security features into one lock as well as monitoring features.Thus, we have high security, comfortable opening, and closing systems, and features that help us easier and faster, all requirements do not conflict and help to make our homes safer than before. Today, the provision of a home security system has become an important study in adopting the latest technology to achieve this goal. Wireless network is one of the technologiesused to provide remote monitoring and control of household items. This paper aims to propose a key departmental security system based on Raspberry pi technology where cameras, keypad and pi-lids are used to provide a terrific powerful system to notify the owner, and to inform visitors by giving them a User ID. For this reason, only authorized people will be allowed to enter the departments.The system works by capturing guests with a summary with a code and a camera mounted on the doors at the same time, such snippets will be sent to the owner. The proposed system could beexpanded to accommodate various facilities and services such as banks and offices.